Level of Understanding of Palembang Aviation Polytechnic Cadets on Aviation Fire Rescue Rules and Regulations - Komalasari, Yeti; Utama, Wira Dharma (Graduate Program Magister Manajemen Pendidikan, 2022)
This study was conducted to determine the level of understanding of Palembang Aviation Polytechnic cadets on aviation fire rescue rules and regulations. Aviation fire rescue rules and regulation is one of the courses in the education curriculum of the Diploma III Aviation Fire and Rescue Study Program (PPKP) Palembang Aviation Polytechnic which was obtained in the first semester. The type of research used in this study is a quantitative type with a cross sectional research design. This study aims to see the average difference in the pre-test and post-test scores so that the paired sample t-test analysis test was carried out. The results of the study are expected to measure the level of understanding of cadets on aviation fire rescue regulations through a pre-test as the average basic knowledge of cadets of aviation fire rescue rules and regulations, then intervention through education and training of aviation fire rescue rules and regulations material and a reassessment is carried out to get the average post-test results. So that the success indicator data is obtained through the increase in the results of the pre-test and post-test.